A thematic review on the implementation of heutagogy in universities - Mohamad, Siti Nurul Mahfuzah; Hairi, Fairuzza; Pinandita, Tito; Saad, Sahrudin (Little Lion Scientific, 2022)
Smart technology, artificial intelligence and robotics have recently become the focus of the new industrial revolution, which now influences our daily lives. The process of teaching and learning at higher education institutions needs to be updated to meet the challenges of Industry 4.0. Different types of learning spaces and pedagogies, such as heutagogy, are required. Although heutagogy has been practised for a long time, there is a deficiency in studies which review the existing literature about implementing heutagogy. In light of this fact, this article is, therefore, a systematic review of the literature on the application of heutagogical methods in universities worldwide. This study utilized publications from 2016 to 2020 from databases such as Web of Science, Scopus, ACM Library, Science Direct, Emerald Insight, Taylors & Francis Online, as well as from the alternative database Google Scholar. The search efforts resulted in a total of 23 articles that can be systematically analyzed according to the Preferred Reporting Items for the Systematic Reviews and Meta-Analysis (PRISMA). By using ATLAS. ti 8 as a tool, this review has five main themes, namely, i) ICT; ii) Blended Learning; iii) Outside Classroom Activities; iv) Distance Learning and; v) Module or Curriculum Related. The results showed that heutagogy is a suitable approach that can be applied in this era and that it is recommended that this approach be implemented during this COVID-19 season. Finally, at the end of this research, a number of recommendations for future scholars will be discussed.